2020
DOI: 10.3390/cancers12113395
|View full text |Cite
|
Sign up to set email alerts
|

Outcome After 68Ga-PSMA-11 versus Choline PET-Based Salvage Radiotherapy in Patients with Biochemical Recurrence of Prostate Cancer: A Matched-Pair Analysis

Abstract: The purpose of this analysis was primarily to analyze biochemical-recurrence free survival (BRFS) after positron emission tomography (PET)-guided salvage radiotherapy (sRT) in a large cohort, and to further compare BRFS after PSMA vs. choline PET/ computer tomography (CT)-based sRT. This retrospective analysis is based on 421 patients referred for PSMA or choline PET/CT after radical prostatectomy due to biochemically recurrent or persistent disease. BRFS (PSA: 0.2 ng/mL) was defined as the study endpoint. Cox… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
11
3

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 11 publications
(15 citation statements)
references
References 47 publications
(21 reference statements)
1
11
3
Order By: Relevance
“…On the other hand, this study, thanks to a median follow-up higher than that found in the literature [ 31 , 32 , 33 ], i.e., 42.2 months, demonstrated the prolonged efficacy of treatment using RT guided by PET/CT on both BR-FS and ADT-FS in the PET-PSMA group. The differences in duration of BR-FS and ADT-FS between the two groups could be explained by the more exhaustive PSMA PET/CT assessment when the PSA is ≤2 ng/mL due to the known performances of the two radiopharmaceuticals [ 8 , 9 , 10 , 11 , 12 , 13 , 14 , 15 , 16 ].…”
Section: Discussioncontrasting
confidence: 53%
See 3 more Smart Citations
“…On the other hand, this study, thanks to a median follow-up higher than that found in the literature [ 31 , 32 , 33 ], i.e., 42.2 months, demonstrated the prolonged efficacy of treatment using RT guided by PET/CT on both BR-FS and ADT-FS in the PET-PSMA group. The differences in duration of BR-FS and ADT-FS between the two groups could be explained by the more exhaustive PSMA PET/CT assessment when the PSA is ≤2 ng/mL due to the known performances of the two radiopharmaceuticals [ 8 , 9 , 10 , 11 , 12 , 13 , 14 , 15 , 16 ].…”
Section: Discussioncontrasting
confidence: 53%
“…To our knowledge, 3 major points in our study need to be underlined and allow it to stand out in the literature, namely, the 3 studies comparing the efficacy of treatment focused on oligo-recurrences using RT guided by FCH or PSMA in clinical routine for PC recurrence [ 31 , 32 , 33 ]. The main results of these studies are detailed in Table S1 .…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…New imaging methods with improved sensitivity and specificity will affect radiotherapy planning for future patients with recurrent prostate cancer. The diagnosis of lymph node metastases enables treatment planning upfront of both local recurrence and lymph node metastases [28] , [29] . However, still a large proportion of these patients will have either no lymph node metastases or possibly findings of uncertain value.…”
Section: Discussionmentioning
confidence: 99%